Madeline in London - Bemelmans, Ludwig, 1898-1962. (New York : Viking, 1961)
When the Ambassador moves to London, the twelve little girls go to visit his son, Madeline has an adventure on a horse, and the horse returns to Paris with the girls.
Keywords: Madeline (Fictitious character) -- Juvenile fiction; Horses -- Juvenile fiction; Madeline (Fictitious character) -- Fiction; Horses -- Fiction; Stories in rhyme; London (England) -- Juvenile fiction; London (England) -- Fiction